Antiatherogenic activity of silybin in Wistar rats: an experimental study - Senthil, G.; P., Venkata Naveen Kumar; Raja, T. A. R.; Reddy, R. V. Rama Narayana (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Dyslipidemia is the major contributor to an increased risk of atherosclerosis. Furthermore, Atherosclerosis presently comprises one of the essential contributors to a global epidemic of cardiovascular disease and turn out to be the leading cause of death and disability worldwide. Natural antioxidants have been shown to be effective in reducing lipid profiles and mitigate peroxidative modification of lipoproteins and atherosclerosis. The aim of the study was to explore the antiatherogenic effect of silybin through its antioxidant mechanism in Wister rats fed on hypercholesterolemic diet. Methods: Male Wistar rats of 150-200 g were used for this study. Hypercholesterolemia in rats was induced by administration of high cholesterol diet. The Wister rats were divided into four groups, each with eight rats. After 60 days blood samples were drawn by retro-orbital puncture for biochemical analysis. The animals were sacrificed by cervical dislocation and liver and aorta were dissected out and processed for histopathological study and biochemical analyses. Results: In the histopathological study high cholesterol fed Wister rats showed fatty degeneration of hepatocytes with leucocytic infiltration of sinusoids. The level of TBARS was significantly increased in high cholesterol diet fed rats (p<0.05). Silybin at both doses [300 mg/kg (1593.00±81.08) and 600 mg/kg (1596.00±28.81)] reduced the plasma TBARS significantly (p<0.05). The antioxidant enzyme levels were also reduced significantly in high cholesterol diet fed rats (p<0.05). Conclusions: The study suggests a conclusive evidence of silybin has antiatherogenic action. Its safety profile, availability and low cost are an added advantage to the presently available pharmacological therapy. Hence, silybin can be considered in conjunction with other available dyslipidemic medication in the market.